Adaptation of forced migrant children in general educational institutions: a case study of primary school-aged children from Ukraine - Vsevolod V. Konstantinov; Natalya A. Mali (Peoples' Friendship University of Russia (RUDN University), 2020)
The unstable situation in the modern world leads to an ever-increasing number of forced migrants in Russia from different regions. In most cases, forced migration is a critical, traumatic, extreme and frustrating situation. The events in Ukraine caused the emergence in Russia of forced migrants, including school-aged children, who were given the opportunity to continue their education in Russian schools. It can be assumed that the stressful traumatic situation, in which these children found themselves, negatively affected their physical and mental state, which in the future may affect the process of their school adaptation. Studying the specifics of the school adaptation of children who experienced the stressful traumatic situation of forced migration at the stage of primary general education, it is possible to solve the problem of organising adaptation measures in a general educational institution. The aim of the research was to study the specifics of the adaptation of forced migrant children in general educational institutions (through the example of primary school-aged children from Ukraine). The study involved 241 children, of whom 121 were permanent residents of Penza studying in local educational institutions and 120 were forced migrant children from Ukraine who began their studies in Penza schools. To identify the indicators of the emotional and social-psychological components of their school adaptation, the "Draw-A-Non-Existent Animal" and "DrawA-Family" tests were used; and E. Wagner's "Hand Test" was used for diagnosing aggressiveness. It was revealed that the school adaptation of forced migrant children from Ukraine as compared with that of their Russian peers has certain specific features, which are more evident in the characteristics of its emotional and social-psychological components. The results of the study can be used in organizing psychological and pedagogical support for forced migrant children during the process of their school adaptation.